ANALISIS UNSUR INTRINSIK DALAM KUMPULAN CERITA RAKYAT KALIMANTAN BARAT - Mira Juliawati; Aprima Tirsa; Asep Eka Nugraha (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2022)
Abstract : This research is motivated by the problem in this research is the lack of knowledge of students about literary works in the form of folklore that exist in their area, while in Indonesian Language Learning in Elementary School students are required to be able to know the folklore in their area of origin and understand the contents of a folklore. which can be reviewed through the elements contained in the folklore text. Lack of attention from the public, both the general public and students in preserving the folklore inherited from their ancestors, especially the folklore in the West Kalimantan area, makes the development of folklore less known, the lack of children's concern for folklore is due to the development of science and technology, therefore researchers feel the need for a breakthrough by describing the results of the analysis of the intrinsic elements in the three West Kalimantan folk tales. The method in this research is descriptive analysis method. The data collected through this research is qualitative data in the form of words or sentences contained in folklore texts. Data collection techniques used in this study were observation, literature study and content analysis. Based on the research results from the analysis of the intrinsic elements of the three folk tales originating from three different areas in West Kalimantan which include themes, trees, plot, setting, viewpoints and mandates, it can be concluded that West Kalimantan folklore has interesting elements to be introduced to society and in elementary school learning can help students' interest in learning local folklore. Keywords : analysis of intrinsic elements of folklore, Indonesian.Abstrak: Penelitian ini dilatar belakangi permasalahan yaitu kurangnya pengetahuan siswa tentang karya sastra berupa cerita rakyat yang ada didaerahnya sedangkan dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar siswa dituntut untuk dapat mengetahui cerita rakyat yang ada di daerah asalnya dan memahami isi dari sebuah cerita rakyat yang dapat ditinjau melalui unsur-unsur yang terkandung dalam teks cerita rakyat. Kurangnya Perhatian dari masyarakat, baik umum maupun pelajar dalam melestarikan cerita rakyat yang diwariskan nenek moyang khususnya cerita rakyat yang ada didaerah Kalimantan Barat membuat perkembangan cerita rakyat kurang diketahui, kurangnya kepedulian anak terhadap cerita rakyat disebabkan perkembangan IPTEK, oleh karena itu peneliti merasa perlu adanya suatu terobosan dengan mendeskripsikan hasil analisis terhadap unsur-unsur intrinsik pada tiga cerita rakyat kalimantan Barat. Metode dalam penelitian ini adalah metode deskriptif analisis. Data yang dikumpulkan melalui penelitian ini adalah data kulaitatif yang berupa kata atau kalimat yang terdapat dalam teks cerita rakyat. Teknik Pengumpulan data yang digunakan dalam penelitian ini adalah observasi, studi pustaka dan analisis isi. Berdasarkan hasil penelitian dari analisis unsur intrinsik ketiga cerita rakyat yang berasal dari tiga daerah berbeda dikalimantan barat yang meliputi tema, penokohon, alur, latar, sudut pandang dan amanat dapat disimpulkan bahwa cerita rakyat kalimantan barat memiliki unsur-unsur yang menarik untuk diperkenalkan pada masyarakat dan dalam pembelajaran disekolah dasar dapat membantu minat siswa untuk mempelajari cerita rakyat daerahnya sendiri.Kata Kunci : Analisis Unsur Intrinsik Cerita Rakyat, Bahasa Indonesia